2015
DOI: 10.1503/jpn.140154
|View full text |Cite
|
Sign up to set email alerts
|

Lower white matter microstructure in the superior longitudinal fasciculus is associated with increased response time variability in adults with attention-deficit/hyperactivity disorder

Abstract: IntroductionAttention-deficit/hyperactivity disorder (ADHD) is characterized by a pervasive pattern of age-inappropriate inattentive behaviour and/or impulsiveness and hyperactivity. Although ADHD is often viewed as a childhood disorder, it also affects 2.5% of adults, 1 which has profound negative implications for the patients themselves, their social environment and society. The pathophysiology of ADHD is still poorly understood owing in part to its substantial clinical and etiological heterogeneity. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 51 publications
(85 reference statements)
4
34
1
Order By: Relevance
“…Rather, RTV is thought to reflect lapses in attention that produce a skewed reaction time distribution with a large tail (Leth-Steensen et al, 2000). More thorough investigation of RTV used ex-Gaussian modeling and showed that increased RTV is partly due to overly slow responses (Feige et al 2013; Gmehlin et al, 2013; Wolfers et al, 2015). These slow responses are reflected by the ex-Gaussian parameter tau , which represents the exponential component of the reaction time distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, RTV is thought to reflect lapses in attention that produce a skewed reaction time distribution with a large tail (Leth-Steensen et al, 2000). More thorough investigation of RTV used ex-Gaussian modeling and showed that increased RTV is partly due to overly slow responses (Feige et al 2013; Gmehlin et al, 2013; Wolfers et al, 2015). These slow responses are reflected by the ex-Gaussian parameter tau , which represents the exponential component of the reaction time distribution.…”
Section: Discussionmentioning
confidence: 99%
“…These slow responses are reflected by the ex-Gaussian parameter tau , which represents the exponential component of the reaction time distribution. Recently, we showed that the tau parameter was associated with the microstructural integrity of the right superior longitudinal fasciculus, a white matter tract implicated in both attention and ADHD (Wolfers et al, 2015). Taken together, such findings suggest a neurobiological basis for within-subject variability in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…It is also correlated with response time variability in attention-deficit hyperactivity disorder (Wolfers et al, 2015). However in Williams Syndrome, fractional anisotropy of the superior longitudinal fasciculus is increased relative to controls, and high fractional anisotropy is associated with poor visuospatial performance (Hoeft et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned arcuate fasciculus, which interconnects Wernicke's and Broca's areas, is also considered to be part of this pathway. Reduced FA in the superior longitudinal fasciculus has been observed in children and adults with ADHD (Hamilton et al., ; Wolfers et al., ), bipolar disorder (Benedetti et al., ; Frazier et al., ), major depression (Lai & Wu, ) and schizophrenia (Clark et al., ; Melicher et al., ).…”
Section: Morphometry – Overviewmentioning
confidence: 99%
“…The previously mentioned arcuate fasciculus, which interconnects Wernicke's and Broca's areas, is also considered to be part of this pathway. Reduced FA in the superior longitudinal fasciculus has been observed in children and adults with ADHD (Hamilton et al, 2008;Wolfers et al, 2015), bipolar disorder (Benedetti et al, 2011;Frazier et al, 2007), major depression (Lai & Wu, 2014) and schizophrenia (Clark et al, 2012;Melicher et al, 2015). Sun et al (2015) recently reported that first episode individuals with schizophrenia can be clustered into two groups: one with pervasive white matter deficits and another with deficits limited specifically to the superior longitudinal fasciculus.…”
Section: Corpus Callosum and Additional Fibre Tractsmentioning
confidence: 99%